MPLEMENTASI MODEL PEMBELAJARAN THINK PAIR SHARE PADA MATA PELAJARAN SEJARAH DI KELAS XI IPS 1 SMA NEGERI 1 TORUE - Ni Luh Sriasih; Mutawakkil Mutawakkil (Scolae: Journal of Pedagogy, 2019)
The formulation of the problem in this article are (1) How is the implementation of the Think Pair Share learning modelin history subjects in class XI IPS 1 of SMA Negeri 1 Torue ?. (2) What are the obstacles faced by teachers inimplementing Think Pair Share learning models in history subjects in class XI IPS 1 of SMA Negeri 1 Torue? Thepurpose of this article is (1) to explain the implementation of Think Pair Share learning models in history subjects inclass XI IPS 1 of SMA Negeri 1 Torue. (2) explain the obstacles faced by teachers in implementing Think Pair Sharelearning models in history subjects in class XI IPS 1 of SMA Negeri 1 Torue. This article is a qualitative research. Datacollection techniques used were observation, interview, and documentation techniques. Based on the results of the studyshowed that the implementation of the Think Pair Share method in history subjects in class XI IPS 1 of SMA Negeri 1Torue went well. The initial step in implementing this learning model is the Think stage: giving a problem to studentsthen giving some time to think, the next step is the Pair stage: forming students into groups each consisting of twostudents (classmates) , the final step is Share: students present the results of their discussion to the front of the class.Think Pair Share learning model makes students more active in asking questions and doing the assignments given bythe teacher, besides that students become more confident because they are trained to explain the results of the discussionin front of the class. The obstacles faced by the teacher in implementing Think Pair Share learning models in historysubjects are (a) Limited time which causes the teacher difficulty in guiding students more individually, besides the timefor presentations in front of the class takes longer because the student groups are formed more. (b) There is a passivepartner, only one person doing the task so they are not paired in solving problems but copy the answers from theirpartners. (c) The number of students in one class is an odd number, so that there is only one person left without apartner